The U.P. DMST Administrative Office a systems and procedures study - Ines, Romeo Jr (College of Engineering, 1989)
Work Distribution 1. Objectives of the Dept. 2. Task Lists 3. Work Distribution Analysis 4. Recommendations Layout-Workflow Analysis 1. Present Layout 2. Layout Flow Analysis 3. Work Simplification 4. Recommendation Forms Design and Control 1. CMT Cadet's Record Card 2. Green Card 3. CMT Transcript of Records 4. UP CMT Certification 5. Certification for Graduation 6. Alien Information Sheet 7. Forms Processes